Influence of partial immersion on steel plate dynamic properties - Kůrečka, Jan; Habán, Vladimír (EDP Sciences, 2019)
Eigenfrequency of object drops when it is submerged in the water compared to an air exposition. In this article the effect of partial submersion on dynamic properties of steel plate is investigated. Changes differ by a type of particular modeshape because of relative position of nodes and antinodes to free surface. Dynamic properties are influenced mainly by position of antinodes, in which maximal displacement occurs. Comparison of experiment, FEM simulation in ANSYS and custom code analytical solution is presented. Added effects of fluid on the steel plate are discussed.

Eigenfrequency of object drops when it is submerged in the water compared to an air exposition. In this article the effect of partial submersion on dynamic properties of steel plate is investigated. Changes differ by a type of particular modeshape because of relative position of nodes and antinodes to free surface. Dynamic properties are influenced mainly by position of antinodes, in which maximal displacement occurs. Comparison of experiment, FEM simulation in ANSYS and custom code analytical solution is presented. Added effects of fluid on the steel plate are discussed.
Influence of partial immersion on steel plate dynamic properties
Keywords: eigenmodes; eigenfrequency; eigenmodes; eigenfrequency